Administration of estates in Malaysia: Jurisdiction and misconception - Drs Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini; Md Said, Muhamad Helmi; Abdul Manap, Siti Nuramani (Universiti Utara Malaysia Press, 2017)
The administration of estate formally commences upon the application by the beneficiaries to the related administrative bodies.The application marks the beginning step in the administration of estate since the application is an essential process in obtaining the letters of representation. With the existence of multiple administrative bodies in Malaysia, one needs to ensure that the application is made to the right administrative body. Furthermore, the administration of estate needs to be promptly settled to avoid any unwanted consequences, hence justifying the need for the early application by the beneficiaries. However, some beneficiaries deliberately stall the application, which is detrimental to the administration of estate. Confusion in identifying the right administrative body as well as the wrong perception of the beneficiaries of the administrative bodies have been identified as the causes behind the late application. This paper addressed the jurisdiction of the administrative bodies in the administration of the deceased’s estate in Malaysia through the comparative approach in classifying the different roles and authorities of each administrative body. The writing involved the research method by way of a library-based study whereby the data were collected from multiple sources including conference papers, textbooks, statutes, case laws, journals and other materials.The finding points out several suggestions including the need for collaboration between the society and the government in relaying the information regarding the actual impression of the administrative bodies in the administration of estate.